Nonlinear 3D path following control of a fixed-wing aircraft based on acceleration control. (May 2019) - Galffy, A.; Böck, M.; Kugi, A.
Abstract: This paper focuses on the design of a novel path following control concept for fixed-wing aircraft, which systematically incorporates the nonlinearities of the flight dynamics. By introducing an acceleration based inner loop control, feedforward acceleration demands of nonlinear 3D paths can be directly taken into account. Furthermore, the nonlinear effects of airspeed, orientation, and gravity are considered separately by implementing a cascaded design and feedback linearization. As a result, robust performance of the path following control is achieved even for wind speeds in the order of the aircraft's airspeed and path accelerations significantly higher than the gravitational acceleration. By further including direct lift control, a high-bandwidth vertical acceleration control is developed. Results of flight experiments show that the designed control concept is particularly beneficial in terms of the tracking performance for 3D paths, the incorporation of input constraints, the robustness against wind and turbulence effects, and the ease of implementation as well as the low computational complexity.